Genome-wide analysis of transcriptomic divergence between laboratory colony and field Anopheles gambiae mosquitoes of the M and S molecular forms - Aguilar, Ruth (2010)
Our knowledge of Anopheles gambiae molecular biology has mainly been based on studies using inbred laboratory strains. Differences in the environmental exposure of these and natural field mosquitoes have inevitably led to physiological divergences. We have used global transcript abundance analyses to probe into this divergence, and identified transcript abundance patterns of genes that provide insight on specific adaptations of caged and field mosquitoes. We also compared the gene transcript abundance profiles of field mosquitoes belonging to the two morphologically indistinguishable but reproductively isolated sympatric molecular forms, M and S, from two different locations in the Yaoundé area of Cameroon. This analysis suggested that environmental exposure has a greater influence on the transcriptome than does the mosquito’s molecular form-specific genetic background.